An Analytical Evaluation of Semiconductor Resistance Changes in Weak Magnetic Fields - Akkus, Adem (Recent Contributions to Physics, 2025)
Variations in electrical resistance under the influence of magnetic fields play a crucial role in numerous technological applications, including hard disk drives and microcircuit sensors. In this study, the change in the electrical resistance of a semiconductor exposed to a weak magnetic field is examined within a generalized theoretical framework. The analysis is carried out by formulating the system using single-parameter Fermi–Dirac distribution functions. For all calculations, an analytical expression for these functions, proposed by one of the authors, is employed. A comparison between the analytical results and those obtained through numerical methods demonstrates a high degree of agreement, confirming the reliability and accuracy of the proposed formulation. The analytically derived results are presented in tabular form to enhance clarity and facilitate direct comparison.